Policies on Regulatory Reform in Indonesia: Some Proposals - Chandranegara, Ibnu Sina; Ali, Muhammad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
After the reformation, the number of laws and regulations has continued to increase. In the period 2000-2017, there were 35,901 regulations have been issued. The highest number is Regional Regulations, which are as many as 14,225 Regional Regulations, followed by a Ministerial Regulation at 11,873. In the third place, there were 3,163 regulations from non-ministerial institutions. This study has main objectives of finding policy choices in an effort to simplify and identify regulations as an agenda for legal reform. This research is a normative juridical research. The data used are secondary data, which includes primary and secondary legal materials, in the form of relevant legislation, as examples of regulations that are out of sync, incoherent, and potentially overlapping. This study concluded that the regulatory reform agenda can be carried out by three means, i.e. (1) Regulatory simplification (2) Reconceptualization of understanding regulatory needs and (3) synergies between regulators. There must be also some reformation between actual practice and long term frameworks on regulation making process and regulation itself. That is because effective regulation is not just predicated on technical information-capturing capabilities (and the experience) of the regulator.